Implementation of A Clean and Healthy Lifestyle Based on Vedic Scriptures After The Covid 19 Pandemic - Ayu Wahyuni, I Dewa (International Journal of Multidisciplinary Sciences, 2024)
This paper aims to describe how the application of a healthy living culture based on the Vedic scriptures after the covid 19 pandemic. This research is a descriptive qualitative research involving students of UPT SMPN 1 Tellu Limpoe. Data collection was done through interviews and observations. Data analysis uses analysis of the results of observations related to the application of a healthy living culture according to the Vedic scriptures after the covid 19 pandemic. Analysis of the results of interviews related to clean and healthy lifestyles at SMPN 1 Tellu Limpoe. The results showed that (1) the application of a clean and healthy lifestyle through activities to keep the school environment clean. And the application of yoga in extracurricular learning the type of yoga taught is hatta yoga with stages starting from prayer, stretching asanas, core asanas, relaxing asanas, pranayama, and ending with simple meditation. From the results of the interview, it was found that there were cognitive changes in students' learning concentration after the implementation of a healthy living culture at SMPN 1 Tellu Limpoe.